2023
DOI: 10.54910/sabrao2023.55.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability for Yield, Oil Content, and Physio-Biochemical Characters of Canola (Brassica Napus L.) Under Salt Stress Conditions

S.F. ALSHARARI,
A.A. IBRAHIM,
S.A. OKASHA

Abstract: Creating a half-diallel cross succeeded among seven diverse canola genotypes. The obtained 21 F1 hybrids with their seven parents underwent three salinity stress levels exposure—3.91 dsm1 (Normal), 6.24 dsm-1 (S1), and 7.81 dsm-1 (S2) —during the 2020/2021 growing seasons. Salinity treatments significantly reduced days to 50% flowering, plant height, number of primary branches, pods/plant, 1000-seed weight, seed yield/plant, seed oil content, relative water content, calcium, potassium, and the ratio between K+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Notably, this study revealed that the application of GABA had a significant impact on mitigating the negative effects of salinity stress on wheat plants. Additionally, GABA treatment increased the levels of antioxidant defense elements in wheat cultivars, regardless of the severity of the stress conditions [ 23 , 75 ]. The proline content increased when salt stress and GABA were applied simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, this study revealed that the application of GABA had a significant impact on mitigating the negative effects of salinity stress on wheat plants. Additionally, GABA treatment increased the levels of antioxidant defense elements in wheat cultivars, regardless of the severity of the stress conditions [ 23 , 75 ]. The proline content increased when salt stress and GABA were applied simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…8A). Principal component analysis (PCA) was conducted on the morphological and biochemical traits of various wheat genotypes to assess the grouping and relationships between the studied genotypes under different salt stress conditions [15,23]. According to Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations